Fostering Academic Entrepreneurship: New Insights into Incubation from an Evolutionary Perspective - Marina Geenhuizen van (European Regional Science Association (ERSA), 2003)
This paper explores obstacles in the growth of academic start-ups and potential policies to overcome these obstacles. To this purpose the focus is on start-ups from Delft University of Technology in the Netherlands as an example. First, by adopting an evolutionary perspective, including notions from resource based theory, obstacles to growth are identified and explored. Second, an explanatory framework of growth is developed and tested using multivariate analysis. The main explanatory variables are lack of marketing knowledge, dealing with uncertainty, use of supporting measures and size of the starting team. Third, these results and structural changes in knowledge production and use serve as an input for the design of a number of policy options from the perspective of co-evolution.
Keywords: 330